Instant Yii 1.1 Application Development Starter. - Mumm, Jacob (Packt Publishing, 2013)
Get to grips with a new technology, understand what it is and what it can do for you, and then get to work with the most important features and tasks. A concise guide that delivers immediate results with practical recipes that give you useful hints and tips on avoiding the pitfalls in Eclipse 4 development. This book is aimed at developers with some basic programming experience and a general understanding of relational databases, or anyone who is ready to take their development to the next level with framework-driven development. A basic understanding of MySQL, PHP, HTML, and HTTP is expected.